The Future of Asian Trade Deals and IP - Liu, Kung-Chung; Chaisse, Julien (Bloomsbury Academic, 2019)
The first part of this open access book sets out to re-examine some basic principles of trade negotiation, such as choosing the right representatives to negotiate and enhancing transparency as a cure to the public's distrust against trade talks. Moreover, it analyses how the Comprehensive and Progressive Agreement for the Trans-Pacific Partnership (CPTPP) might impact on the Regional Comprehensive Economic Partnership's (RCEP) IP chapter and examines the possible norm setters of Asian IP. It then focuses on the People's Republic of China's (PRC) trade and IP strategy against the backdrop of the power games between the PRC, India and the US. The second part of the book reflects on issues related to investor-state dispute settlement and its relationship with IP, such as how to re-calibrate the balance in international investment arbitration, and whether compulsory license of IP constitutes expropriation in India, the PRC and select ASEAN countries. The third part of the book questions and strives to improve some of the proposed IP provisions of CPTPP and RCEP and to redefine some aspects of international IP norms, such as: pre-grant patent opposition and experimental use exception; patent term extension; patent linkage and data exclusivity for the pharmaceutical sector; plant variety protection; pre-established damages for copyright infringement; and the restructuring of copyright limitations in the public interest. The open access edition of this book is available under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com. Open access was funded by the Applied Research Centre for Intellectual Assets and the Law in Asia, School of Law, Singapore Management University.